Lorentz Force Damping Mechanism in Non-Uniform Magnetic Fields and Its Application in Vibration Isolation - Huang, Zian (Transactions on Computer Science and Intelligent Systems Research, 2025)
This study delves deeply into the theoretical basis of the Lorentz force damping mechanism in non-uniform magnetic fields and its application potential in the field of vibration isolation. By establishing the dynamic model of the rectangular coil in the gradient magnetic field and combining it with the numerical simulation system, the nonlinear enhancement relationship between the magnetic field gradient and the damping performance was analyzed. The research verified the significant strengthening effect of the magnetic flux change rate of the gradient magnetic field on the damping effect, revealing that increasing the magnetic field gradient can effectively enhance the system response speed and vibration suppression capability, while reducing the circuit resistance further optimizes the energy dissipation efficiency. In the extended model, the synergistic effect of position-dependent nonlinear damping force and elastic restoring force has been systematically analyzed. This technology offers an innovative solution for vibration control in the industrial field.
Keywords: Lorentz Force Damping; Non-uniform Magnetic Fields; Vibration Isolation; Gradient Magnetic Field Optimization.